Study of Compressive Strength of Cellular Lightweight Concrete (CLC) Bricks Using Empty Palm Fruit Bunch Ash (EPFBA) as an Additive - Benny Setiawan; Ahmad Hamidi (JACEE (Journal of Advanced Civil and Environmental Engineering), 2024)
The rapid advancement of scientific knowledge in the construction field has spurred research on Cellular Lightweight Concrete (CLC) bricks by incorporating Empty Palm Fruit Bunch Ash (EPFBA). This study focuses on CLC bricks with the addition of EPFBA at 1%, 1.5%, and 2% of the cement weight, which are then compared with CLC bricks without EPFBA. These bricks undergo compressive strength testing at 7,14, and 28 days following the testing method specified in SNI 8640-2018. The specimen curing process is conducted at room temperature for three consecutive days, with thrice daily watering. The compressive strength test results at 28 days indicate that CLC bricks without EPFBA yield 2.11 MPa, CLC bricks with the addition of 1% EPFBA yield 1.06 MPa, CLC bricks with the addition of 1.5% EPFBA yield 1.95 MPa, and CLC bricks with the addition of 2% EPFBA yield 2.33 MPa. In conclusion, the addition of EPFBA to CLC bricks at 28 days enhances the compressive strength of CLC bricks.